Film Review. THE ZONE OF INTEREST (Jonathan Glazer, US/UK/PL 2023) - Boes, Elena (Journal for religion, film and media, 2025)
Review of Jonatahan Glazer's award-winning historical fiction drama THE ZONE OF INTEREST.